PENGARUH PEMBERIAN PAKAN ALAMI ARTEMIA SALINA DAN ROTIFERA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP LARVA IKAN NILA SALINE (Oreochromis niloticus) - Amidra, Amidra; Ya'la, Zakirah Raihani; Tantu, Fadly Y (AgriSains, 2017)
Research was aimed to study the effect of live feed Artemia salina and Rotifera on growth and survival rates of larva saline nile tilapia (Oreochromis niloticus). Research was counducted from March to April 2015 in Balai Budidaya Air Payau (BBAP) Takalar, Mapakalompo Village, Galesong Subdistrict, Takalar District, South Sulawesi. The fish was maintained in the 15 litre basin with density of 2 ind/litre. Larva fed according to the treatments: A (100% Artemia salina), B (100% Rotifera) and C ( 50% Artemia salina and 50% Rotifera) three times a day and was weighed three time a day during the research (12 days). Absolute growth and survival rates of each experimental unit was accounted at the end the experimental. the experimental was completely randomize designed with three treatments and six replicates. Results growth (1,54), while the highest survival rates (86,66%) was achieved at 50% Artemia salina feeding.Â  Â Keywords: Larva Saline Nile Tilapia, Artemia Salina, Rotifera, Growth, Survival